Importance of strategic regional management in ensuring area safety - Horčička, Aleš (Univerzita Pardubice, 2010)
The article deals with the problems of strategic regional management in the Czech Republic. The aim of strategic management development activities in a regional background is to be successful in achieving objectives in the form of meeting citizen interests and needs in the managed localities and to support ensuring area safety. On that ground, cooperation of all included municipal subjects is necessary. Their cooperation is based on the equal participation principle. The main benefit has to be in the field of utility for all participants (regional and micro-regional clusters) in the process of regional development.
Keywords: regions and micro-regions; strategy; strategic regional management; safety management; area safety